Affective disorders and сognitive impairment in the early stages of Parkinson’s disease - Gulnara Zh. Makhmudova; Niinoya I.N. Vellovich; Elena V. Shirshova (Клиническая практика, 2022)
Background: Parkinson's disease (PD) is an age-related neurodegenerative disease in developed countries. The prevalence of PD ranges from 41 per 100,000 in the fourth decade of life to more than 1,900 per 100,000 in people over 80 years of age. Neurodegeneration associated with Parkinson's disease probably occurs several decades before the onset of motor symptoms. Affective and cognitive impairments are one of the most frequent non-motor manifestations of PD, which can lead to a number of adverse outcomes. Aim: to evaluate affective and cognitive impairments in patients at the early stages of PD. Methods: 61 patients with PD participated in the study. All the participants were divided into two groups depending on the presence or absence of a diagnosis of depression verified by psychiatrists: Group 1 was the main group (n=48), group 2 was the control group (n=13). The control group included patients without depression. The average age of the participants was 62.29.6 years. The analysis of the PD stages was carried out in both groups. In the main group, stage II PD was diagnosed in 75%, in the control group in 31% of patients. The average duration of the disease was 2.51.6 years. A clinical examination was carried out using the Beck depression questionnaire, apathy scale, Spielberger anxiety questionnaire and anxiety assessment scale in PD (to assess emotional disorders), cognitive function assessment scale in PD (SHOBP-Cog, Scopa-Cog), digital symbol replacement test (symbols-numbers test), Montreal assessment Scale cognitive functions (MoCA test), a test for connecting numbers and letters, and a Stroop test (for evaluating cognitive functions). Results: It was revealed that in the early stages of PD, the prevalence of depression, clinically significant apathy, personal and reactive anxiety was high. Significantly higher rates of depression severity, depression level, apathy level and personal anxiety were noted among the patients with stage II PD compared to the patients with stage I PD. There was a marked tendency to a decrease in cognitive functions at stage I of PD, aggravated at stage II of the disease, which was confirmed by the results of the tests: a low level of cognitive functions on the Montreal scale was detected in 52%; 70% of patients, regardless of the PD stage, showed a low rate of completion of the 1st and 2nd parts of the Stroop test for their age; the results of the digital character replacement test were below normal in 75% of cases. Conclusion: The most common affective disorders in the early stages of PD are depression and anxiety. Apathy and depression have a negative impact on the cognitive functions of patients, which worsen with the progression of the disease.